Stewartship and evolving fidelity in a Scottish fire festival - McKean, Thomas A. (Traditiones (Ljubljana), 2012)
This paper looks at a Scottish fire festival, the "burning of the Clavie" at Burghead in the North East of Scotland, and its practitioners in relation to external authorities, particularly the police and regional political administrators. Internal and external pressures for change and stability are examined and author explores the negotiation between insiders and outsiders that co-create the ritual as it is practiced today.
Keywords: ethnology; Etnologija; customs; Šege; Rituali; Škotska; rituals; ljudski prazniki; ljudski običaji